In vivo targeted molecular magnetic resonance imaging of free radicals in diabetic cardiomyopathy within mice. (September 2015) - Towner, R. A.; Smith, N.; Saunders, D.; Carrizales, J.; Lupu, F.; Silasi-Mansat, R.; Ehrenshaft, M.; Mason, R. P.
Abstract Free radicals contribute to the pathogenesis of diabetic cardiomyopathy. We present a method for in vivo observation of free radical events within murine diabetic cardiomyopathy. This study reports on in vivo imaging of protein/lipid radicals using molecular MRI (mMRI) and immuno-spin trapping (IST) in diabetic cardiac muscle. To detect free radicals in diabetic cardiomyopathy, streptozotocin (STZ)-exposed mice were given 5, 5-dimethyl-pyrroline-N-oxide (DMPO) and administered an anti-DMPO probe (biotin–anti-DMPO antibody–albumin–Gd–DTPA). For controls, non-diabetic mice were given DMPO (non-disease control), and administered an anti-DMPO probe; or diabetic mice were given DMPO but administered a non-specific IgG contrast agent instead of the anti-DMPO probe. DMPO administration started at 7 weeks following STZ treatment for 5 days, and the anti-DMPO probe was administered at 8 weeks for MRI detection. MRI was used to detect a significant increase (p < 0.001) in MRI signal intensity (SI) from anti-DMPO nitrone adducts in diabetic murine left-ventricular (LV) cardiac tissue, compared to controls. Regional increases in MR SI in the LV were found in the apical and upper-left areas (p < 0.01 for both), compared to controls. The biotin moiety of the anti-DMPO probe was targeted with fluorescently-labeled streptavidin to locate the anti-DMPO probe in excised cardiac tissues, which indicated elevated fluorescence only in cardiac muscle of mice administered the anti-DMPO probe. Oxidized lipids and proteins were also found to be significantly elevated (p < 0.05 for both) in diabetic cardiac muscle compared to controls. It can be concluded that diabetic mice have more heterogeneously distributed radicals in cardiac tissue than non-diabetic mice.